Sintesis Karbon Aktif dari Kulit Salak dengan Aktivasi K2CO3 sebagai Adsorben Larutan Zat Warna Metilen Biru - Arenst Andreas (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The preparation of activated carbon from salacca peels was studied by chemical activation with potassium carbonate (K2CO3). Salacca peels were firstly impregnated at a fixed salacca peel to potassium carbonate ratio of 1:2 and fixed potassium carbonate concentration of 10 %-w. The impregnated salacca peel were then carbonized in an electrical furnace at temperature of 800 °C. Macroporous activated carbons with a high surface area of 888.9 m2/g were obtained. The activated carbon was tested in the adsorption of methylene blue (MB) from aqueous phase. The adsorption study was realized using batch experiments with synthetic MB solution with various initial concentration of 2, 4, 6, 8 and 10 ppm. The Freundlich, Langmuir, Temkin and Dubunin-Radushkevich adsorption models were used for mathematical description of the adsorption equilibrium, and it was found that the experimental data fitted very well to the Langmuir isotherm. Batch adsorption studies, based on the assumption of a pseudo-first-order, pseudo-second-order or intraparticle diffusion mechanism, showed that the kinetic data followed closely a pseudosecond- order rather than a pseudo-first-order mechanism. The adsorption capacity of salacca peel based activated carbons for the removal of MB was found to be 405 mg· g-1. These results clearly indicated the salacca peel derived activated carbons as a potential adsorbent for removal of MB from aqueous solutions.